The 21st Century Life Skills-Based Education Implementation at the Non-Formal Education Institution - Prasetyo, Iis; Suryono, Yoyon; Gupta, Sachin (Universitas Negeri Semarang, 2021)
Life skills education basically aims to improve the quality of human resources to overcome various problems in their daily lives in the era of the 21st century. This study was aimed to describe the non-formal education institution managers’ efforts to implement the 21st-century life skills education. The researcher employed the quantitative approach with a survey research design in Yogyakarta City and Sleman District. The respondents were non-formal education institution managers. The data were collected using questionnaires and analyzed using the quantitative analysis method. The results of the study show that the implementation of 21st-century life skills education is still limited to the knowledge and hard skill developments. The unexplored materials include thinking skills which consist of conceptual thinking, creativity, innovation, problem-solving, critical thinking, decision-making, and metacognition. The novelty of this research is the findings in this study provide a more detailed description of the weaknesses of non-formal education institutions in providing life skills education.